The National Education Act, 1978 - UNESCO (1978)

Mind in society: Development of higher psychological processes - Vygotsky, Lev Semyonovich (Harvard University Press, 1978)
The great Russian psychologist L. S. Vygotsky has long been recognized as a pioneer in developmental psychology. But his theory of development has never been well understood in the West. Mind in Society corrects much of this misunderstanding. Carefully edited by a group of outstanding Vygotsky scholars, the book presents a unique selection of Vygotsky's important essays.